2002
DOI: 10.1034/j.1600-0544.2002.02213.x
|View full text |Cite
|
Sign up to set email alerts
|

Deciduous tooth crown size and asymmetry in strabismic children

Abstract: Asymmetries in the head area, such as promoted here in strabismic children, may have associations with asymmetries in the dentition, focusing the embryonal origins and timing of developmental processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
(38 reference statements)
0
1
0
1
Order By: Relevance
“…Genetic, molecular and anthropometric studies have shown that tooth crown growth during embryonal and foetal periods is partly under the control of genes and partly environmentally controlled . Family studies have indicated that permanent tooth crown size heritability estimates are ranging from 35 to 90%, while in the primary dentition, generation heritability line studies are rare, due to obvious difficulty in chronological comparisons between two generations, but twin comparisons have shown that deciduous teeth have a stronger genetic component than permanent teeth in crown size determination .…”
Section: Introductionmentioning
confidence: 99%
“…Genetic, molecular and anthropometric studies have shown that tooth crown growth during embryonal and foetal periods is partly under the control of genes and partly environmentally controlled . Family studies have indicated that permanent tooth crown size heritability estimates are ranging from 35 to 90%, while in the primary dentition, generation heritability line studies are rare, due to obvious difficulty in chronological comparisons between two generations, but twin comparisons have shown that deciduous teeth have a stronger genetic component than permanent teeth in crown size determination .…”
Section: Introductionmentioning
confidence: 99%
“…Ao longo dos anos, diferentes métodos têm sido propostos para o estudo da anatomia interna dos dentes permanentes e decíduos. Em relação aos dentes decíduos foram realizados estudos utilizando modelos de gesso, para avaliação da forma e tamanho da coroa dental (Heikkinen;Alvesalo;Tienari, 2002;Barberia et al, 2009), radiografias digitais (Poornima e Reddy, 2008), microscopia eletrônica de varredura (Kumar, 2009;Luglie et al, 2012), diafanização (Gupta e Grewal, 2005;Bagherian et al, 2010). Esses métodos são destrutivos e produzem mudanças irreversíveis nos espécimes.…”
Section: Introductionunclassified